Pluriversality Is Already Here (KULT_online, 2022)
Pluriversal Politics: The Real and the Possible by Arturo Escobar is an inspirational book that seeks to offer hope in the middle of the civilizational crisis we are facing. The collection of eight essays is a call to recognize the existence of different worlds — or different ontologies — and the radical interdependence that binds all of us — human, nonhuman, and more-than-human. Beyond enriching our imagination with the possibilities of re-existence enacted by indigenous or Afro-descendant peoples from Abya Yala, the book offers some theoretical tools for extending thought.